2018
DOI: 10.1016/j.anai.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

SQ house dust mite sublingual immunotherapy tablet subgroup efficacy and local application site reaction duration

Abstract: Treatment with 12 SQ-HDM consistently improved symptoms and was well tolerated in relevant subgroups of subjects with HDM AR/C. Local application site reactions to 12 SQ-HDM were typically mild to moderate and transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…[31][32][33] In the present study, scRNA-Seq was performed in a larger number of male subjects with good response; therefore, the possibility of sex affecting Foxp3 cannot be denied. However, the effect of SLIT has not been reported to vary by sex, 34,35 Currently there are no biomarkers for evaluating the efficacy of SLIT, 36 and any increase in Treg numbers should be reflected in a greater expression of Foxp3; however, this has also not been clearly established. Thus, presumably the effect of SLIT resides in actual functionality of the cells, which is difficult to assess according to an increase or decrease in transcription factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In the present study, scRNA-Seq was performed in a larger number of male subjects with good response; therefore, the possibility of sex affecting Foxp3 cannot be denied. However, the effect of SLIT has not been reported to vary by sex, 34,35 Currently there are no biomarkers for evaluating the efficacy of SLIT, 36 and any increase in Treg numbers should be reflected in a greater expression of Foxp3; however, this has also not been clearly established. Thus, presumably the effect of SLIT resides in actual functionality of the cells, which is difficult to assess according to an increase or decrease in transcription factor levels.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of SLIT treatment in humans, 60-85% of patients show mild local and self-limiting reactions; only a small number of patients (0.05-7%) show more severe adverse reactions that lead to discontinuation of the treatment. 16,31 In dogs, only very mild and self-limiting adverse effects have been reported, such as pruritus, vomiting, lethargy and decreased appetite. 15 In the present study, no systemic or local adverse effects were observed, although one cat was withdrawn as a consequence of treatment difficulty related to pre-existing stomatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers ask for an overall score for the AIT to be given at each year of treatment where zero is where there was worsening of rhinitis after 1 year with therapy and the maximum score where there was marked improvement 31 , 49 , 51 . Studies also emphasize the need to have questionnaires for specific scoring regarding adverse effects 32 , 35 , 37 , 38 , 40 . Quality of life questionnaires have been added in several trials 16 , 35 , 40 , 41 .…”
Section: Clinical Questions: Evidence Analysismentioning
confidence: 99%
“…SLIT is generally well tolerated, even at high doses, with good clinical safety [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] . In the vast majority of patients undergoing SLIT, the predominant adverse effects are mild or moderate oral reactions, such as itching, and mouth and throat irritation.…”
Section: Question 4: Is Sublingual Immunotherapy Safe In Allergic Rhi...mentioning
confidence: 99%
See 1 more Smart Citation